IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH DASAR DALAM PEMBENTUKAN PRIBADI SISWA - Rohyana, Hadi; Siddiq, Rifqi Fajar; Maryati (JISPE Journal of Islamic Primary Education, 2024)
This study aims to explore the importance of character education in elementary schools in shaping good personal traits in students. The method used in this research is qualitative with a descriptive approach. Data were collected through in-depth interviews with teachers, observations of school activities, and document analysis related to character education programs implemented in several elementary schools in Indonesia. Data analysis was conducted thematically to identify patterns and main themes emerging from the collected data. The results of the study indicate that character education in elementary schools plays a significant role in shaping good personal traits in students. Structured and consistent character education programs help students develop values such as honesty, responsibility, cooperation, and respect for others. Teachers act as role models by demonstrating these values in their daily actions. Additionally, active participation from parents and the school community is found to be an important factor in supporting the effectiveness of character education. The conclusion of this study is that character education in elementary schools is crucial for shaping good personal traits in students. The implementation of effective character education programs requires collaboration between schools, teachers, parents, and the community. To enhance the success of character education, it is recommended that schools integrate character values into the curriculum and daily activities and provide training for teachers on teaching and assessing character education. Thus, it is hoped that character education can become a strong foundation for the moral and ethical development of students in the future